P-025 Hospitalizations and Characteristics of Patients with Ulcerative Colitis and Crohn's Disease Treated with Vedolizumab in the United States. (March 2016) - Reynolds, Matthew; Raluy-Callado, Mireia; O'Hara, Don; Alam, Naufil; Smyth, Michael; Khalid, Mona
Abstract : Background: Vedolizumab (VDZ), a humanized monoclonal antibody that targets α4β7 integrin, was approved in May 2014 by the U.S. Food and Drug Administration for the treatment of moderate to severely active Crohn's Disease (CD) or Ulcerative Colitis (UC). In CD and UC, hospitalizations are an important treatment outcome; previous research using U.S. administrative claims data has reported 26%–30% of patients with CD are hospitalized within 6 months of initiating anti-TNF treatment. 1 The aim of this study was to investigate treatment with VDZ in a real-world clinical practice setting by describing the characteristics of patients with CD and UC initiating VDZ, and the trend in all-cause and IBD-related hospitalizations pre- and post VDZ initiation. Methods: This retrospective cohort study employed electronic health records from the U.S. Explorys Universe database to identify patients with a diagnosis of CD or UC (CD: ICD-9 555.xx; UC: ICD-9 556.xx). Patients who initiated VDZ between 06/01/14 and 02/24/15, with ≥1 year of medical history and ≥180 days follow-up, were included. Demographic and clinical characteristics and prior medication use were investigated at the time of first VDZ infusion. Both all-cause and IBD-related hospitalizations in the 180 days pre- and post-VDZ initiation were described. Results: Two hundred thirty-seven (62%: female) patients (71%: CD; 29%: UC) met the inclusion criteria. The mean age at first VDZ infusion and time since diagnosis was 43 years (standard deviation [SD]: 15.7) and 5.2 years (SD: 3.5), respectively. At index, median C-reactive protein level was 1.4 mg/dL (inter-quartile range: 0.7–2.9, n = 48) 17% (n = 40) of patients had no previous history of biologic therapy whereas 83% (n = 197) of patients had ≥1 biologic (46.0%: adalimumab, 45.1%: infliximab, 25.3%: certolizumab pegol, 4.2%: golimumab, 5.1%: natalizumab); 26% (n = 52) and 8.0% (n = 19) of patients had 2 and ≥3 prior biologic therapies, respectively. Within the 90 days prior to first VDZ infusion, 44.3% (n = 105) patients had ≥1 prescription of corticosteroids. 38.0% (n = 90) of patients had prior surgery, while 32.5% of patients with CD (n = 55) had history of fistulizing disease: 7.1% of whom had active fistulizing disease at VDZ initiation. Compared to the 180-day period before the first VDZ infusion, in the 180-day period after, the proportion of patients with ≥1 all-cause hospitalizations decreased from 20.7% (95% Wilson score Confidence intervals [CI]: 16.0–26.3) to 14.3% (CI: 10.5–19.4). Patients with ≥1 IBD-related hospitalizations also decreased from16.0% (CI: 11.9–21.2) to 11.4% (CI: 7.9–16.1). Conclusions: Results from this multi-center, real-world study on the use of VDZ found that 17% of patients were biologic naive when initiating VDZ. The majority of patients had received biologic therapy previously, indicating these patients likely had refractory disease. The proportion of patients with all-cause and IBD-hospitalizations were lower in the 180 days post-VDZ initiation than in the 180 days prior to VDZ treatment, suggesting a positive impact of VDZ on reducing hospitalizations in patients with UC and CD. Further studies with larger cohorts are required to confirm this trend.